Recursos directamente recaudados y su incidencia en la ejecución presupuestal de la gerencia regional de transporte y comunicaciones, periodo 2018 – 2022 - Aguilar Manzur, Saraid (2024)
Between 2018 and 2022, the Regional Transportation and Communications Management showed a variable budget execution in terms of income and expenses. The revenue collected, which started at 2,184,938.00 S/ in 2018, showed a decreasing trend, reaching a minimum of 675,502.00 S/ in 2022. This drop in revenue reflects challenges in resource collection or changes in financial policies. On the other hand, expenses experienced significant fluctuations, with a dramatic increase in 2022, reaching 22,733,300.00 S/. Compared to that year's income, this high expense suggests a possible large investment or an extraordinary expense not reflected in previous years. Expenses in 2018 to 2021 were relatively stable and in line with income, except for a notable difference in 2022. The discrepancy between total income (6,266,288.00 S/) and total expenses (28,144,522.00 S/) during the period indicates a deficit considerable, which implies that the Regional Management could have depended on other sources of financing or incurred debt to cover expenses. Analysis of the distribution of income and expenses also reveals the importance of conducting regular audits and adjusting collection strategies to ensure greater stability and financial balance in the future.